AFFORDING STUDENTS’ WORK-ABILITY IN CAMPUS PUBLIC SPACES - Rasyid Fauzan Akbar; Murni Rachmawati; Didit Novianto (Center for Scientific Publication, 2026)
This study addresses the increasing prevalence of informal learning activities and the corresponding demand for public places within academic environments that effectively afford the work-ability function. The research specifically investigates how students at Institut Teknologi Sepuluh Nopember, Surabaya, utilize various public places—originally not intended as workspaces—to support their academic tasks. Focusing on six locations (Canteen, Mosque, Plaza, Library (office), and Dormitory Hall), the study explores the phenomenon of students affording workrelated activities in unconventional settings. The research employs qualitative observation methods, dismantling the theory of affordance through three analytical lenses: Architectural Structure, User Interpretation, and Behavior Response. These components allow for an in-depth understanding of how spatial conditions contribute to user adaptability. Data collected from on-site observations were further analyzed using the Sorensen Similarity Coefficient, generating a similarity index within the range of >0 to ≤1. An index value above 0.500 is considered indicative of a significant link between specific architectural elements and affording work-ability. Findings reveal that students afford work-ability through: (1) the adaptation of multipurpose architectural structures, (2) the effective use of expansive floor areas with open layouts, (3) engagement with accessible and userfriendly environments that enable flexible use, and (4) reliance on adequate shading systems as part of the enclosure elements. These insights contribute to the evolving discourse on responsive campus design, emphasizing the need for spatial adaptability that reflects actual user behavior beyond predefined functional intentions.